Intestinal Transplant Registry Report: Global Activity and Trends. Issue 1 (1st December 2014) - Grant, D.; Abu‐Elmagd, K.; Mazariegos, G.; Vianna, R.; Langnas, A.; Mangus, R.; Farmer, D. G.; Lacaille, F.; Iyer, K.; Fishbein, T.; on behalf of the Intestinal Transplant Association
<x xml:space="preserve">Abstract</x> The Registry has gathered information on intestine transplantation (IT) since 1985. During this time, individual centers have reported progress but small case volumes potentially limit the generalizability of this information. The present study was undertaken to examine recent global IT activity. Activity was assessed with descriptive statistics, Kaplan–Meier survival curves and a multiple variable analysis. Eighty‐two programs reported 2887 transplants in 2699 patients. Regional practices and outcomes are now similar worldwide. Current actuarial patient survival rates are 76%, 56% and 43% at 1, 5 and 10 years, respectively. Rates of graft loss beyond 1 year have not improved. Grafts that included a colon segment had better function. Waiting at home for IT, the use of induction immune‐suppression therapy, inclusion of a liver component and maintenance therapy with rapamycin were associated with better graft survival. Outcomes of IT have modestly improved over the past decade. Case volumes have recently declined. Identifying the root reasons for late graft loss is difficult due to the low case volumes at most centers. The high participation rate in the Registry provides unique opportunities to study these issues.